Water, settlement and food provision in Natal Colony: The Winterton Irrigation Settlement, 1902-1904 (Historia, 2021)
Irrigation settlements formed a vital part of infrastructural history in the former Natal Colony. Projects implemented in the late nineteenth century had a specific socio-political impetus, which shifted to a more economic strategy after the South African War. The Tugela irrigation schemes were intended as an official long term investment in food security and to diversify the potential of crop production. After 1902, the Upper Tugela Irrigation Scheme at Winterton and the Lower Tugela Irrigation Scheme at Muden were planned: both aimed at creating small, irrigated farms on which to settle "a different class of farmer", in the case of the former, medium to low income white settlers; and the latter, African farmers. Using an interface of the social and the physical, this article will discuss the Winterton Irrigation Settlement contextualised with environmental and social issues affecting food production in the 1890s. It will begin with the schematic master-plan allowing for the settlement, and discuss the identification of lands, physical construction of the water infrastructure and the surveys of the plots. It then discusses the social engineering that allowed for the allocation of lands, before commenting on the invisible role function of the furrows as ongoing infrastructure and a means of underpinning social sustainability.
Keywords: Water history; Winterton; irrigation; engineering works; social sustainability; food security